Not in my backyard: the obligation to grant places of refuge to ships in need of assistance - Jachs, Brent (Institute of Marine and Environmental Law, 2016)
Oceans cover 70% of the world's surface and are a source of 90% of the world's biomass. Oceans provide the world's populations with food and facilitate international trade in goods. The shipping industry is a notable source (although not leading source) of marine pollution both from operational discharges and maritime incidents. With a vast number of ships navigating the world's oceans the impact of maritime incidents, especially of bulk carriers of oil, on the marine environment can be devastating. Ships which become distressed often attempt to find a 'place of refuge', being nearby port or a sheltered area within the territorial waters of a nearby coastal state. Traditionally these ships in distress had the customary law right of entry into port in order to ensure that persons on board could be saved. This position seems to have changed in the modern age. With the advancement of modern technology persons on board can be saved without bringing the distressed ship into port. In addition, these ships in distress present a serious risk to the marine environment within the waters of the coastal state. Coastal state practice seems to indicate that coastal states prioritise the preservation of their own sovereign waters over the needs of the particular ship in distress, especially where there is no risk to human life. It would seem that the traditional customary law rights of ships in distress do not apply to circumstances where there is no risk to the persons on board and where there is only a risk to the marine environment. These ships are now commonly called ships in need of assistance and are differentiated from ships in distress due to the fact that the risk is one to the marine environment and not to human life. The result of the refusing places of refuge creates the problem of ships in need of assistance as such ships proceed to beg for entry from other nearby coastal states usually being refused along the way. Through the discussion of notable maritime incidents of this nature it will be shown that such refusal of entry by coastal states into a place of refuge is a leading factor that increases the probability of a maritime incident occurring and thereby increasing the likelihood of damage to the marine environment. The concept of state sovereignty has been utilised as a justification for coastal states refusing entry into a place of refuge. This dissertation will discuss the concept of coastal state sovereignty paying particular attention to the legislative and enforcement rights of coastal states in the regulation of pollution and the protection of the marine environment. The international community has long since recognised that the protection of the marine environment is a general state duty and a principle of international customary law. The duty to protect and preserve the marine environment guides, informs and restricts coastal state action. This dissertation analyses the relationship between sovereignty and the duty to protect the marine environment in the context of ships in need of assistance in modern international law. This dissertation seeks to conclude with an overall analysis of the current customary and modern international law rights of ships in need of assistance in order to determine whether coastal states are obliged to grant places of refuge. The IMO Guidelines will be discussed to analyse whether same add any value to the problem of ships in need of assistance and to what end such guidelines indicate further development on this issue.